Metabolomic signatures of intestinal colonization resistance against Campylobacter jejuni in mice - Shayya, Nizar W.; Bandick, Rasmus; Busmann, Lia V.; Mousavi, Soraya; Bereswill, Stefan; Heimesaat, Markus M. (Frontiers in Microbiology, 2023)
Campylobacter jejuni stands out as one of the leading causes of bacterial enteritis. In contrast to humans, specific pathogen free (SPF) laboratory mice display strict intestinal colonization resistance (CR) against C. jejuni, orchestrated by the specific murine intestinal microbiota, as shown by fecal microbiota transplantation (FMT) earlier. Notably, CR of SPF mice was abrogated by antibiotic microbiota depletion in secondary abiotic (SAB) mice and in SAB mice recolonized with a human microbiota (hma mice) but restored in SAB mice recolonized with a murine microbiota (mma mice). We used these murine infection models to investigate intestinal metabolomes in line with the specific murine enteric microbiota composition associated with CR in fecal samples. Quality controls by culture and culture-independent analyses confirmed that the microbiota was depleted in SAB mice, and that the FMT in hma and mma mice was successful. In comparison to hma mice, the murine intestinal microbiota of mma and SPF mice (with CR against C. jejuni) contained significantly elevated numbers of lactobacilli, and Mouse Intestinal Bacteroides, whereas numbers of enterobacteria, enterococci and Clostridium coccoides group were reduced. Targeted metabolome analysis revealed that fecal samples from mice with CR contained increased levels of secondary bile acids and fatty acids with known antimicrobial activities, but reduced concentrations of amino acids essential for C. jejuni growth as compared to control animals without CR. These metabolomic signatures provide evidence that microbiota-mediated nutrient competition and antibacterial activities of intestinal metabolites act together in driving murine CR against C. jejuni.